Vitamin D Deficiency, Obesity and Diabetes - Li, Y-X; Zhou, L (Cellular and Molecular Biology, 2015)
Obesity and type 2 diabetes mellitus (T2DM) are main chronic diseases harming human health. Although the association between obesity and T2DM is well established, the molecular mechanism is still unclear. Accumulating evidence suggests vitamin D plays a role in the development of these diseases. Vitamin D is a necessary nutrient for humans. People usually do not pay attention to supplementing vitamin D, since vitamin D can be produced when their skin is exposed to the sunlight. Nevertheless, even in highly sunny regions, vitamin D deficiency exists, suggesting vitamin D deficiency is a global problem. Vitamin D deficiency has previously been considered only to influence bone metabolism. Accumulating evidence counters this opinion. In vivo studies have revealed that vitamin D deficiency reduces insulin secretion capacity of the islet beta cells in pancreas. Moreover, epidemiological studies have demonstrated that vitamin D deficiency is closely related to obesity and increased risk of T2DM. This review introduces the current work on vitamin D, obesity and diabetes.